HUBUNGAN PERAN PETUGAS KESEHATAN DAN MEDIA INFORMASI DENGAN PENGETAHUAN REMAJA PUTRI TENTANG NYERI HAID DI SMP NEGERI 3 KOTA LANGSA TAHUN 2016 - Elly Susilawati (Poltekkes Kemenkes Surabaya, 2017)
The objective of this research is to identify The Relationsheep Between The Role of Healthcare Officers and Information Media with The Tenage Girl’s Knowledge about The Massage Therapy to Reduce The Menstrual Pain at Public Junior High School 3 Kota Langsa.The research method used is descriptive research method with cros sectional design, where the independent variable (risk factor) is the role of midwife and information media while the independent variable (effect) is the teenage girl’s knowledge about massage therapy to reduce the menstrual pain. Both of these variables are observed simultaneously at the same time. The population in this study were all female students of class IX Year 2016 at Public Junior High School 3 Langsa Kota who experienced primary menstrual pain (175 female students). This research was conducted at Public Junior Hugh School 3 Langsa Kota in September 2016.The results of this study show that 135 out of 175 total respondents (77.1%) have sufficient knowledge, 87 out of 175 total respondents (49.7%) said that there is no role of healthcare officers, and 48 out of 175 total respondents (37.4%) said that there is a role healthcare officers.In addition, the results of this study also indicate that 23 out of 28 well-informed respondents (13.1% of total respondents) said that there is a role of healthcare officers, while 5 out of 28 respondents who have good knowledge (2.9% of total respondents) said that there is no role of healthcare officers.The results of this study also show that 8 out of 12 respondents who have less knowledge (4.6% of total respondents) said that there is a role of healthcare workers, while 4 out of 12 respondents who have less knowledge (2.3% of total respondents) said that there is no role of healthcare officer.In the other hand, the results of this study indicate that 78 out of 135 respondents with sufficient knowledge (44.6% of total respondents) said that they got information about massage therapy to reduce menstrual pain from mass media, while 57 out of 135 respondents who had sufficient knowledge (32.6% of total respondents) said that they were not informed about massage therapy to reduce menstrual pain from the mass media.Moreover, the results of this study show that 23 out of 28 well-informed respondents (13.1% of total respondents) said that they got information from the mass media, while 5 out of 28 well-informed respondents (2.9% of total respondents) said that they were not informed about it from the mass media.Futhermore, the results of this study show that 6 out of 12 respondents with less knowledge (3.4% of total respondents) said they got information from the mass media while 6 out of 12 respondents with less knowledge (3.4% of total respondents) said they did not get Information from mass media.Based on the results of this study, the researcher concluds that there is a significant relationship between the role of healthcare officers in providing information about massage therapy to reduce menstrual pain and knowledge of respondents, where the result of Chi-Square test showed P value ≤ 0.00. In addition, the researcher also concluds that there is a relationship between information variables about massage therapy in reducing menstrual pain from mass media, which was obtained by respondents, and knowledge of respondents, where the result of Chi-Square test showed P value ≤ 0.04.Keywordshealthcare officers, information media, massage therapy, menstrual pain.